Enhancement in the Selectivity and Sensitivity of Ni and Pd Functionalized MoS2 Toxic Gas Sensors. Issue 10 (12th June 2020) - Chacko, Levna; Massera, Ettore; Aneesh, P. M.
Abstract : Atmospheric pollution is one of the major aspects of concern which led to the research of sensors for the detection of toxic gases. The supreme surface-to-volume ratio makes two-dimensional MoS2 a promising material to be used as an electronic sensor. Here, we demonstrate the fabrication of a high-performance gas sensor based on atomic-layered MoS2 nanoflakes synthesized by a facile hydrothermal process. Structural and morphological studies confirmed the formation of few-layered phase pure hexagonal MoS2 nanoflakes. The results demonstrate that the Pd-MoS2 layers exhibited a very high relative response to NO gas (700%) at 2 ppm concentration with a minimum NO detection limit of 0.1 ppm and Ni-MoS2 demonstrated a relative response of 80% towards H2 S gas with a limit of detection of 0.3 ppm with good repeatability and selectivity, owing to the increased adsorption energy of NO on Pd-MoS2 and H2 S on Ni-MoS2 through the formation of PdNOx and NiS2 complexes respectively. The improved sensing performance of this MoS2 -based sensor also suggests the great potential and possibility of MoS2 related 2D materials and its combinations for the development of futuristic highly sensitive nanosized gas sensors suitable for anti-pollution automotive system and as volatile biomarkers.